RELEVANSI DALEM KAWEDANAN BEKONANG SEBAGAI BANGUNAN CAGAR BUDAYA BERDASARKAN UU RI NOMOR 11 TAHUN 2010 - Ivan Prapanca Wardhana (Keraton: Journal of History Education and Culture, 2019)
This article discusses the relevance of Dalem Kawedanan Bekonang both in terms of function and building based on the Law of the Republic of Indonesia Number 11 the Year 2010 About Cultural Heritage and understands the current condition of Dalem Kawedanan Bekonang in terms of building functions and functions. Dalem Kawedanan Bekonang is an important historical place for the development of Sukoharjo Regency, but it is unfortunate that most of the people are future children who do not yet have historical stories in their own environment. To get results that can be trusted and can answer answers that are in line with what is expected in achieving research objectives used historical research by obtaining social. From the description that has been conveyed, we can conclude that: The Dalem Kawedanan Bekonang Building is still relevantly referred to as a Cultural Heritage Building according to the criteria set forth in Law of the Republic of Indonesia Number 11 the Year 2010 Concerning Cultural Heritage.